THE IMPLEMENTATION OF TPACK APPROACH IN TEACHING ENGLISH AT SMP N 17 MEDAN - Monika Situmorang; Johannes Jefria Gultom (Universitas Negeri Medan, 2023)
The research purpose was to investigate the implementation of TPACK Approach in teaching English at SMP Negeri 17 Medan using descriptive qualitative research methods, and observation and interview data collection techniques. Based on the research, it is known that the first teacher implement TPACK by using mobile phones. Unlike the second teacher, she applies technological knowledge by using digital tools such as laptops, projectors and mobile phones and combining learning materials from various sources such as internet and YouTube. The components above are listed in the lesson plan prepared by the teacher. For the second problem, it was found that both teachers implemented TPACK in this way because it was adjusted to the abilities, school facilities, and also the students' backgrounds. Therefore, based on all the items on the observation check list, there are 14 items applied by the first teacher and 24 items applied by the second teacher.